Exploring the Impact of Video Project-Based Learning on Student Engagement and Learning Outcomes in Fiqh at Madrasah Ibtidaiyah - Ismail; Tini; Ismaya; Hadi Pajarianto; Dahlan Muchtar (Journal of Southeast Asian Islam and Society, 2025)
Video Project-Based Learning (VPBL) is increasingly recognized as an effective approach to enhancing student engagement and learning outcomes. This study examines the impact of VPBL on Fiqh education at Madrasah Ibtidaiyah Negeri (MIN) 2 Enrekang, focusing on student comprehension, creativity, and pedagogical effectiveness. Employing a pre-experimental design, the study utilized a one-group pretest-post-test methodology to assess changes in student understanding before and after VPBL implementation. The research also incorporated qualitative insights from teacher interviews to provide a comprehensive evaluation. The results reveal a significant improvement in students' comprehension of Fiqh, as evidenced by a 20.53% increase in post-test scores. Video project assessments demonstrate students' ability to creatively interpret and apply Fiqh concepts. Teachers reported that VPBL fosters active learning and deeper student engagement but highlighted challenges related to technical skills and time constraints. These findings underscore VPBL's potential as a transformative approach in Islamic education, blending technology with religious instruction to create an interactive learning environment. Future research should explore VPBL's broader applicability and investigate advanced technological integrations, such as artificial intelligence, to further personalize learning experiences in religious studies.